Examining the Legal Foundations of Educational Inequality: An Analysis of San Antonio Independent School District v. Rodrigues - Haapalahti, Nelli (My University, 2024)
This research paper, in the field of law, examines the legal foundation of educational inequality in the United States as a part of an exploratory workshop on current legal issues in the U.S.A. The U.S. Supreme Court’s case San Antonio Independent School District v. Rodriguez provides a foundation for the discussion on the matter. A case argumentation analysis has been conducted with a specific focus on the Courts’ Equal Protection Clause analysis. Versatile scholarly articles have been used to support the arguments made in this research paper. The primary research results suggest that equal educational opportunities should be provided to all schoolchildren, despite their race, wealth, and the affluence of their school district. The use of local property taxation in educational funding disproportionately affects the quality of education in property-poor school districts. Contrary to the decisions made in Rodriguez, education should have been declared as a fundamental interest protected by the Constitution and wealth should have been regarded as a suspect classification. Furthermore, systemic racism and intersectionality raise significant disparities about the inequalities inherent to the educational system in the U.S. There is a need to take equalizing measures in the funding of public education to guarantee equality of opportunity.

Tässä oikeustieteen alan tutkielmassa tarkastellaan koulutuksen eriarvoisuuden oikeudellista perustaa Yhdysvalloissa osana työpajaa, joka käsittelee ajankohtaisia oikeudellisia kysymyksiä Yhdysvalloissa. Yhdysvaltain korkeimman oikeuden tapaus San Antonio Independent School District v. Rodriguez tarjoaa perustan käsiteltävälle problematiikalle. Tutkimusmetodina on käytetty argumentaatioanalyysiä, joka keskittyy erityisesti tuomioistuimen tekemään yhdenvertaisen suojelun pykälän analyysiin. Tämän tutkimuksen väitteiden tueksi on käytetty useita tieteellisiä artikkeleita. Tutkielman tutkimustulokset viittaavat siihen, että kaikille koululaisille olisi tarjottava yhtäläiset koulutusmahdollisuudet heidän ihonväristään sekä perheen ja koulupiirin varallisuudesta riippumatta. Paikallisen kiinteistöveron käyttö julkisen koulutuksen rahoituksessa vaikuttaa suhteettomasti koulutuksen laatuun kiinteistököyhissä koulupiireissä. Toisin kuin tuomioistuimen Rodriguezissa tehdyissä päätöksissä, koulutus olisi pitänyt julistaa perustuslain suojaamaksi perusoikeudeksi ja köyhyyteen olisi pitänyt suhtautua heikompaan asemaan asettavana tekijänä. Lisäksi rakenteellinen rasismi ja puutteet intersektionaalisuuden huomioimisessa nostavat esiin merkittäviä ongelmia Yhdysvaltojen peruskoulujärjestelmässä. Julkisen koulutuksen rahoituksessa olisi ryhdyttävä korjaaviin toimenpiteisiin, jotta yhtäläisten mahdollisuuksien tasa-arvo koulutuksessa olisi mahdollista toteuttaa.
Keywords: Education 1, Equal Protection Clause 2, Systemic racism 3, Koulutus 1, Yhdenvertaisen suojelun pykälä 2, Rakenteellinen rasismi 3